Analysis of Working Hours, Knowledge Management, and Employee Performance Appraisal on Employee Satisfaction at PLTU Asam-Asam - Triyanto, Ade; Sriyono; Setiyono, Wisnu Panggah (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
PLTU Asam-Asam faces challenges in managing working hours, the effectiveness of knowledge management, and the transparency of performance appraisals, which can affect employee satisfaction. This study aims to analyze the impact of working hours, knowledge management, and performance appraisals on employee satisfaction at PLTU Asam-Asam. The research method employs a quantitative approach using the SEM-PLS analysis technique, with a sample of 183 employees collected through a Likert-scale-based questionnaire. The novelty of this research lies in the simultaneous analysis of the three variables within the steam power plant industry context, which has been relatively unexplored in previous studies. The results show that working hours (β=0.222, T=2.507, p=0.012), knowledge management (β=0.258, T=2.577, p=0.010), and performance appraisal (β=0.319, T=3.070, p=0.002) have a positive and significant impact on employee satisfaction, with performance appraisal being the most influential variable. The three variables' interaction also substantially impacts employee satisfaction (β=0.237, T=2.375, p=0.026). These findings confirm that a combination of optimal working hours management, effective knowledge management systems, and transparent performance appraisal mechanisms can enhance employee well-being and satisfaction while encouraging more adaptive human resource management policies.